Use of The Blended and Distance Learning in Studying Electrical Engineering Disciplines; 8th World Conference on Educational Sciences (WCES-2016), 04-06 February 2016, Madrid, Spain - Kuleshova E. O. Elena Olegovna (2016, 2016)
Title screen